Branding Desa Mandiri Sampah: Wujudkan Tata Kelola Sampah yang Berkelanjutan di Gampong Drien Rampak, Johan Pahlawan Kabupaten Aceh Barat - Ikhsan Ikhsan; Akmal Saputra; Vellayati Hajad; Ikhwan Rahmatika Latif; Fadli Afriandi; Yeni Sri Lestari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
This community service program in Drien Rampak Village, Johan Pahlawan Aceh Barat, aimed to establish a sustainable waste management system through the "Branding Desa Mandiri Sampah" approach. Initial assessments revealed low community awareness and participation in waste management, with only 40% of households aware of its importance and 30% practicing waste separation. Through a series of educational outreach and training sessions on waste separation and composting techniques, the program significantly improved these figures. Post-program evaluations showed a remarkable increase in awareness to 85% and household participation in waste separation rose to 70%. Additionally, 50% of households adopted composting practices, with 40% successfully producing stable compost for domestic use. Despite these achievements, challenges such as technical difficulties in composting remain, highlighting the need for ongoing support and education. This initiative demonstrated that community-based approaches can foster substantial behavioral changes, making Drien Rampak Village a model for sustainable waste management that can be replicated in other rural areas.